THE COMBINATION OF COLORS IN THE PAINTINGS (WITH SPECIAL REFERENCE TO THE PAINTER "RAJA RAVI VARMA"): चित्रकृतियों में रंगो का संयोजन (चित्रकार ‘‘राजा रवि वर्मा’’ के विशेष संदर्भ में) - Aggarwal, Sangita (International Journal of Research -GRANTHAALAYAH, 2014)
In the illustration, Rajaravivarma, the painter who created Rango’s "Sparse Creating Property", was born on 29 April 1848 in Kilimannur. His painting interest was promoted by his maternal uncle, his uncle Rajavarma. Seeing his interest in painting, his maternal uncle was very happy and said, "Nothing comes from just teaching man." Some qualities are inherent in it. I will teach you to make colors, colors are made from leaves, flowers, chemical scenes, many castes and colored soils, but the artist has to find the color of his choice. " चित्रण में रंगो की ‘‘ स्प्रेस क्रिएटिंग प्रापर्टी ’’ को रचने वाले चित्रकार राजारविवर्मा का जन्म 29 अप्रैल 1848 ई. में किलीमन्नूर में हुआ। उनकी चित्रकला रूचि को उनकी चित्रांकन रूचि उनके मामा राजवर्मा ने बढावा दिया। चित्रकला रूचि को देखकर उनके मामा अत्यंत प्रसन्नचित्त हुये और कहा कि ‘‘मनुष्य को केवल सिखा देने से कुछ नहीं आता। कुछ गुण उसमें पैदाइशी होते हैं। मैं तुझे रंग बनाना सिखाऊॅंगा, पत्ते, फूल, रासायनिक दृव्य अनेक जाति और रंग की मिट्टी आदि से रंग तैयार होते हैं, लेकिन अपनी मर्जी का रंग तो कलाकार को ही खोजना पड़ता है।’’